Age-Related Changes in Inter-Joint Interactions for Global and Local Kinematics While Standing - Kimiya Fujio; Yahiko Takeuchi (IEEE, 2023)
Inter-joint interactions are involved in human standing. These interactions work not only for global kinematics that control the center of mass (COM) of the entire body, but also for local kinematics that control joint angular movements. Age-related changes in these interactions are thought to cause unstable standing postures in older people. Interactions of global kinematics are known to be deficient owing to aging. However, it is unclear whether the interaction of local kinematics is affected by aging. We investigated the age-related changes in inter-joint interactions, especially local kinematics, during standing. Differences were investigated in these two inter-joint interactions between older and younger adults in three different postures: normal, eyes-closed, and foam-surface standings. The inter-joint interaction for local kinematics was computed using the induced-acceleration analysis with a double-inverted pendulum model and quantified using an uncontrolled manifold approach. Consistent with previous studies, the inter-joint interaction for COM acceleration (global kinematics) deteriorated in older adults. In contrast, the interactions for angular accelerations in the ankle and hip joints (local kinematics) were slightly better in the older adults. Moreover, the individual components of angular acceleration which were induced by net torques from homonymous and remote joints were significantly increased in older adults. Thus, global and local inter-joint interactions are driven by distinct neural mechanisms and the interaction of local kinematics can compensate for the increment of each component of joint angular acceleration in older adults.